2020
DOI: 10.1212/wnl.0000000000008729
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between diurnal cortisol variation and later-life cognitive impairment

Abstract: ObjectiveTo determine whether hypothalamus-pituitary-adrenal axis (HPAA) dysfunction is prospectively associated with global cognitive impairment in later life. ; and for NSHD between 2006-2010 and in 2015. Serial salivary cortisol samples were collected multiple times within a 24-hour period at mean ages 61.2 and 65.9 years in Whitehall II and at age 60-64 years from NSHD participants. Cortisol profile is defined using cortisol awakening response and AM:PM ratio. Cognitive function was measured using the Mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
11
0
1
Order By: Relevance
“…This is evident in regions with high levels of GC receptors, and AD-sensitive areas, such as hippocampus and frontal cortices. Such abnormal glucocorticoid levels have been associated with faster progression to clinical AD stages (Echouffo-Tcheugui et al, 2018;Pietrzak et al, 2017;Tsui et al, 2020;Udeh-Momoh et al, 2019). These findings suggest a strong link between hypersecretion of GCs evident in this set of individuals, and their compromised cognitive function, and clinical progression.…”
Section: Hpaa In Diseasementioning
confidence: 74%
“…This is evident in regions with high levels of GC receptors, and AD-sensitive areas, such as hippocampus and frontal cortices. Such abnormal glucocorticoid levels have been associated with faster progression to clinical AD stages (Echouffo-Tcheugui et al, 2018;Pietrzak et al, 2017;Tsui et al, 2020;Udeh-Momoh et al, 2019). These findings suggest a strong link between hypersecretion of GCs evident in this set of individuals, and their compromised cognitive function, and clinical progression.…”
Section: Hpaa In Diseasementioning
confidence: 74%
“…However, a more recent study carried out with two large longitudinal datasets concluded that loss of diurnal variation in the HPA-axis (a flattened DCS) preceded and contributed to cognitive decline later in life (Tsui et al, 2020). Furthermore, in a long follow-up study, Ennis et al (2017) suggested that cortisol dysregulations may be a preclinical marker of Alzheimer's disease.…”
Section: Perceived Stress Hpa-axis and Cognitive Functioningmentioning
confidence: 99%
“…In healthy older adults, a flattened DCS has been associated with poorer cognition in some cross-sectional studies (Gardner et al, 2019;Stawski et al, 2011), but not in others (Ennis et al, 2016;Hidalgo et al, 2016). Similarly, the association between a flatter DCS and cognitive impairment has been observed in some longitudinal studies (Beluche et al, 2010;Tsui et al, 2020), but two other studies failed to observe this association (Gerritsen et al, 2011;Singh-Manoux et al, 2014). Similarly, greater perceived stress at baseline predicted accelerated cognitive decline in some follow-up studies (Aggarwal et al, 2014;Munoz et al, 2015;Turner et al, 2017), but not in all of them (Chen et al, 2019).…”
mentioning
confidence: 96%
“…In fact, altered cortisol concentrations have been reported in a number of diseases of the central nervous system, such as psychiatric disorders, e.g., posttraumatic stress disorder [ 12 , 13 , 14 ], schizophrenia [ 15 ], depression [ 16 , 17 , 18 , 19 ], anxiety [ 20 , 21 , 22 ], and cognitive impairment [ 23 , 24 , 25 ]. Changes in the peripheral levels of cortisol have also been reported in certain neurodegenerative conditions, such as Huntington’s disease [ 26 ] or Alzheimer’s disease [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a high correlation between salivary cortisol levels and unbound cortisol in plasma and serum, which remains high during the circadian cycle and under different dynamic tests, such as adrenocorticotropic hormone (ACTH) stimulation [ 39 , 40 ]. Since free cortisol represents the biologically active hormone fraction, salivary cortisol measures have early been considered as a better method than serum cortisol for the evaluation of adrenocortical function; however, cortisol measurement in blood and saliva samples should be performed at different timepoints within the same day because of cortisol circadian rhythm, and it is recommended to repeat cortisol measurements in blood and saliva samples in different days since many factors can acutely influence cortisol secretion [ 23 , 24 , 25 , 39 , 40 ]. The role of hypercortisolemia in the pathophysiology of sleep disorders and neuro-psychiatric disorders accompanied by sleep alterations can only be demonstrated through measures that reflect prolonged exposure to cortisol, since such disorders are typically chronic conditions.…”
Section: Introductionmentioning
confidence: 99%